Evaluation of tomato inbred lines for resistance to the tomato yellow leaf curl disease complex in Oman. (August 2018) - Al-Shihi, Adel A.; Hanson, Peter; Al-Sadi, Abdullah M.; Al-Yahyai, Rashid A.; Briddon, Rob W.; Deadman, Michael; Shahid, Muhammad Shafiq
Abstract: Tomato yellow leaf curl disease (TYLCD), caused by viruses of the genus Begomovirus (family Geminiviridae ), is a major constraint to tomato production in Oman. The development of tomato lines with resistance to the viruses that cause TYLCD is an important target for tomato breeding programs worldwide. The study assessed fourteen tomato inbred lines harbouring one or more of five TYLCD resistance genes ( Ty-1/Ty-3, Ty-2, ty-5 ) for resistance against the TYLCD complex in Oman by screening in the field for TYLCD incidence, severity and viral load over two consecutive years. All Ty gene-containing lines performed better than the susceptible controls, with lower disease incidence, severity and viral DNA load. Lines harbouring Ty -2 alone or in combination with other Ty genes performed poorly. A line harbouring only ty -5 performed the best, displaying no symptoms and having the lowest viral load. The presence of a disease enhancing betasatellite in lines harbouring Ty -2 suggests that this may compromise Ty -2 resistance. The results indicate that the Ty genes are useful in Oman as well as other Gulf Cooperation Council countries and should be incorporated into local varieties. Highlights: Investigated the responses of Ty -tomato lines to the TYLCD complex prevalent in Oman. Tomato cultivars carrying different Ty genes have shown a range of resistance levels. Ty -tomato lines showed lower disease incidence, milder symptoms and lower viral loads. There were distinct differences among Ty- tomato lines, where ty-5 performing the best. Invaluable in developing tomato varieties suitable for cultivation in the Oman.